Sustainability education for sustainable development - Erickson, Larry E.; Griswold, Wendy M.; Saulters, Oral S.; Hohn, Keith L. (Kansas State University, 2011)
There is a growing interest in sustainability education in many universities. Existing courses are being modified to add sustainability. At K-State, the Natural Resource/Environmental Science Project, DEN 582, is an example; sustainability is an important consideration in many of the recent projects. Certificate programs with significant sustainability content are being proposed and approved. Sustainability Seminar, CHE 670, and other new sustainability courses have been introduced. K-State offers a Research Experiences for Undergraduates summer program. Five core competencies, systems thinking, anticipatory capacities, normative competency, strategic thinking, and interpersonal skills to work effectively on multidisciplinary teams were presented and discussed at the American Association for the Advancement of Science Fourth Forum on Sustainability Science Programs. This presentation will provide information on sustainability educational developments at Kansas State University and other universities.
Keywords: Sustainability; Systems; Planning; Certificate programs; College courses